2019
DOI: 10.1182/blood-2019-126115
|View full text |Cite
|
Sign up to set email alerts
|

Targeting B-Cell Maturation Antigen (BCMA) with CC-93269, a 2+1 T Cell Engager, Elicits Significant Apoptosis in Diffuse Large B-Cell Lymphoma Preclinical Models

Abstract: B-cell maturation antigen (BCMA), a member of the TNF receptor superfamily, serves as the cell surface receptor for B-cell activating factor (BAFF). Upon binding of BAFF to BCMA, an intracellular signaling cascade is initiated resulting in upregulation of JNK pathway signaling events and NFkB mediated transcription. The canonical expression pattern of BCMA begins on germinal center B-cells and becomes maximally expressed on mature cells such as plasma cells. Given the high degree of expression of BCMA on multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The result is B cell maturation and differentiation into plasma cells [53]. The expression of BCMA has been expressed in B cell lymphoma highlighting its targeting in the potential use for the treatment of DLBCL patients [54][55][56]. Manfroi in a recent work demonstrated that in a significant fraction of DLBCL patients, tumor cells are able to recruit APRIL producing neutrophils through the release of CXCL8 in both GC and non-GC DLBCL subtypes that in turn induce DNA methylation and acetylation, crucial in DLBCL progression [57].…”
Section: Neutrophilsmentioning
confidence: 99%
“…The result is B cell maturation and differentiation into plasma cells [53]. The expression of BCMA has been expressed in B cell lymphoma highlighting its targeting in the potential use for the treatment of DLBCL patients [54][55][56]. Manfroi in a recent work demonstrated that in a significant fraction of DLBCL patients, tumor cells are able to recruit APRIL producing neutrophils through the release of CXCL8 in both GC and non-GC DLBCL subtypes that in turn induce DNA methylation and acetylation, crucial in DLBCL progression [57].…”
Section: Neutrophilsmentioning
confidence: 99%